Biophysical Detection of Diversity and Bias in GPCR Function - Jaeger, Werner; Armstrong, Stephen; Hill, Stephen; Pfleger, Kevin D. (Frontiers in Endocrinology, 2014)
G protein-coupled receptors (GPCRs) function in complexes with a range of molecules and proteins including ligands, G proteins, arrestins, ubiquitin and other receptors. Elements of these complexes may interact constitutively or dynamically, dependent upon factors such as ligand binding, phosphorylation and dephosphorylation. They may also be allosterically modulated by other proteins in a manner that changes temporally and spatially within the cell. Elucidating how these complexes function has been greatly enhanced by biophysical technologies that are able to monitor proximity and/or binding, often in real-time and in live cells. These include resonance energy transfer approaches such as bioluminescence resonance energy transfer (BRET) and fluorescence resonance energy transfer (FRET). Furthermore, the use of fluorescent ligands has enabled novel insights into allosteric interactions between GPCRs. Consequently biophysical approaches are helping to unlock the amazing diversity and bias in G protein-coupled receptor signaling.